Motivasi Petani dalam Berusahatani Padi Varietas Ciherang di Subak Lanyah 1 Bajera, Kecamatan Selemadeg, Kabupaten Tabanan (Jurnal Agribisnis dan Agrowisata, 2025)
Motivation of Farmers in Cultivating Ciherang Variety Rice in Subak Lanyah 1 Bajera, Selemadeg District, Tabanan Regency. The use of new superior varieties is one of the technologies that play an important role in increasing the quantity and quality of agricultural products, one of which is the Ciherang variety. Ciherang rice variety is an innovation that requires intrinsic and extrinsic motivation in adopting, taking action and implementing rice cultivation. This study aims to determine the intrinsic and extrinsic motivation of farmers in farming Ciherang rice varieties in Subak Lanyah 1 Bajera. Sampling of 63 people using a proportional random method. The analysis used in this study is descriptive qualitative using a Likert Scale. The results showed that the level of motivation of farmers in rice farming Ciherang variety was in the medium category with a score of 67.51% on intrinsic motivation while on extrinsic motivation was 64.88%. The more dominant motivation is intrinsic motivation even though these two motivations are in the moderate category. It is recommended that the head of subak Lanyah 1 Bajera coordinate with PPL in terms of controlling pests and diseases, traders are also advised to provide information on rice prices according to market prices so that farmers remain enthusiastic in farming Ciherang varieties of rice.
Keywords: Ciherang variety rice; motivation; subak